2011
DOI: 10.1073/pnas.1100958108
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide network model capturing seed germination reveals coordinated regulation of plant cellular phase transitions

Abstract: Seed germination is a complex trait of key ecological and agronomic significance. Few genetic factors regulating germination have been identified, and the means by which their concerted action controls this developmental process remains largely unknown. Using publicly available gene expression data from Arabidopsis thaliana, we generated a condition-dependent network model of global transcriptional interactions (SeedNet) that shows evidence of evolutionary conservation in flowering plants. The topology of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
247
1
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 220 publications
(255 citation statements)
references
References 43 publications
(42 reference statements)
4
247
1
3
Order By: Relevance
“…S1C). This region of the network contains coexpressed genes that are up-regulated by the germination-stimulating hormone GA and includes an abundance of growth-promoting cell wall remodeling genes (19,25). The spatiotemporal induction of multiple cell expansion-promoting genes from SeedNet was examined, including the xyloglucan endotransglucosylases/hydrolase (XTH) genes XTH9 and XTH19 (26) and the expansins EXPA1, EXPA8, and EXPA15.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S1C). This region of the network contains coexpressed genes that are up-regulated by the germination-stimulating hormone GA and includes an abundance of growth-promoting cell wall remodeling genes (19,25). The spatiotemporal induction of multiple cell expansion-promoting genes from SeedNet was examined, including the xyloglucan endotransglucosylases/hydrolase (XTH) genes XTH9 and XTH19 (26) and the expansins EXPA1, EXPA8, and EXPA15.…”
Section: Resultsmentioning
confidence: 99%
“…To identify genes driving cell expansion in the growing embryo, we examined the germination subnetwork of the condition-dependent gene-correlation network SeedNet (25) (Fig. S1C).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, previous studies have shown that genes related to flowering are expressed in association with seed development and germination. For example, a genome-wide expression correlation network in Arabidopsis showed that maturity-phase transition regulators such as SE, EMBRYONIC FLOWER1, and EARLY BOLTING IN SHORT DAYS are coexpressed with germination-associated genes and affect seed germination (14). Arabidopsis HISTONE MONOUBIQUITINATION1 and 2 (HUB1 and HUB2) genes regulate flowering and seed germination; seeds of hub1 and hub2 mutants displayed reduced seed dormancy (51), and hub1 seeds also exhibit strong thermotolerance to high temperature at germination (52).…”
Section: Discussionmentioning
confidence: 99%
“…Seed dormancy and germination are regulated primarily by the antagonistic actions of the plant hormones gibberellin (GA; promotive) and abscisic acid (ABA; inhibitory), whose synthesis and action vary in response to environmental signals (12). Recent studies indicate that canonical genes regulating flowering, such as FLOWERING LOCUS T (FT) and FLOWERING LOCUS C (FLC), are also involved in the transition from seed dormancy to germination (13)(14)(15)(16), suggesting that seed dormancy and flowering may be coordinately regulated through overlapping molecular pathways.…”
mentioning
confidence: 99%
“…However, targeted networks, focusing on a specific condition, organ, or developmental phase, allow the dissection of fine regulatory switches that will otherwise be obscured through global comparisons (Usadel et al, 2009). One example is the SeedNet, a genome-wide network model describing transcriptional interactions, representing a binary phase transition study, in nongerminating (or dormant) and germinating Arabidopsis thaliana seeds (Bassel et al, 2011). Integration of the expression data at the resolution of developmental stages and in different environmental contexts is expected to generate a high confidence dynamic gene regulatory model (Long et al, 2008).…”
Section: Introductionmentioning
confidence: 99%